Diallyl trisulfide attenuates Pseudomonas aeruginosa virulence via inhibiting quorum sensing. (September 2022) - Li, Wen-Ru; Zhang, Zhi-Qing; Yao, Jun-Wei; Liao, Kang; Zhu, Li-Ping; Shi, Qing-Shan; Huang, Xu-Bin; Xie, Xiao-Bao
Abstract: Diallyl trisulfide (DATS), diallyl disulfide (DADS), and diallyl sulfide (DAS), three sulfur-rich compounds commonly found in garlic, can inhibit Pseudomonas aeruginosa quorum sensing (QS). We previously reported the inhibitory effects of DAS and DADS on the PAO1 QS system. To delineate any differences in QS inhibitory mechanisms among these three compounds and further verify their functional chemical groups, the QS-inhibitory effects and mechanism of DATS on P. aeruginosa PAO1 were investigated based on transcriptomic analysis, qRT-PCR, and physiological and chemical experiments in this study. The results indicated that DATS was mildly toxic to P. aeruginosa PAO1 and inhibited its growth slightly in a dose-dependent manner. Furthermore, DATS downregulated the transcriptional levels of all key genes involved in PAO1 QS systems, including lasI / lasR, rhlI / rhlR, and pqsABCDEH / pqsR, and downregulated the transcriptional levels of some related virulence genes, including the genes encoding exoprotease, elastase, lectin, and rhamnolipids, as well as those involved in PQS, pyocyanin biosynthesis, and biofilm formation. As a result, the production of related virulence factors by the PAO1 strain decreased upon DATS exposure. Therefore, DATS attenuated P. aeruginosa virulence and pathogenicity by inhibiting its QS systems. Through a comparative analysis of the QS-inhibitory effects of DATS, DADS, and DAS on the PAO1 strain, DATS was found to have the strongest QS-inhibitory activity, followed by DADS and DAS. In conclusion, the inhibitory activities of these sulfur compounds against P. aeruginosa QS and virulence were related to the thioether and disulfide groups, which increase with an increase in the number of sulfur atoms in the chemical formula. These findings are of great significance for the control of P. aeruginosa virulence and pathogenicity in the future. Highlights: DATS inhibited PAO1 growth slightly. DATS inhibited all PAO1 QS key genes, including lasI / lasR, rhlI / rhlR, and pqsABCDEH / pqsR. DATS inhibited some virulence genes encoding exoprotease, elastase, lectin, rhamnolipids, PQS, pyocyanin, and biofilm. DATS attenuated PAO1 virulence by inhibiting its QS systems. The QS inhibitory effects were related to the thioether and disulfide groups of DATS.